Pro Apache Beehive - Mittal, Kunal; Kanchanavally, Srinivas; SpringerLink (Online service) (Berkeley, CA : Apress, 2005)
If you want exposure to the new open source lightweight SOA-driven Apache Beehive framework project, then pick up Pro Apache Beehive, the first book on this MVC Web framework, which is increasingly gaining interest in the Eclipse community through Eclipse Pollinate. Author Kunal Mittal addresses specific Beehive topics such as page flows, controls, JSR 181 web services, XMLBeans and more. This book proceeds to describe how these technologies are used in WebLogic Workshop, and how other IDEs are extending support for these technologies. Mittal also compares PageFlows in Workshop to the Standard.
What$1 (Bs Apache Beehive? -- Introducing Web Services and SOA Fundamentals -- Introducing Annotations -- Dissecting Java Page Flows -- Using NetUI and Page Flows -- Using Controls -- Working with Beehive Web Services and JSR 181 -- Using XMLBeans.s
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books